Comparison of Control Algorithms for Shunt Active Filter for Harmonic Mitigation (International Journal of Engineering and Computer Science, 2014)
Shunt Active Filter generates the reference current, that must be provided by the power filter to compensate harmonic currents demanded by the load. This paper presents different types of SRF methods for real time regeneration of compensating current for harmonic mitigation. The three techniques analyzed are the Synchronous Reference Frame Theory (SRF), SRF theory without synchronizing circuit like phase lock loop (PLL) also called instantaneous current component theory and finally modified SRF theory. The performance of Shunt Active Power Filter in terms of THD (Total Harmonic distortion) of voltage and current is achieved with in the IEEE 519 Standard. The comparison of all methods is based on the theoretical analysis and simulation results obtained with MATLAB/SIMULINK